Near-infrared spectroscopy during organ donation in brain-dead patients - Michele Carron; Enrico Tamburini (Indian Journal of Anaesthesia)
Near-infrared spectroscopy (NIRS) is essential for monitoring cerebral oxygenation in anaesthesia and critical care, offering non-invasive insights into regional cerebral oxygen saturation (rSO2). However, extracerebral contamination can compromise NIRS accuracy. The O3™ regional oximetry system, with its advanced multi-wavelength technology, may contribute by providing more accurate measurements. In a study involving brain-dead organ donors, near-normal rSO2 values were initially observed despite cerebral anoxia, suggesting extracerebral signal interference. Following aortic clamping and cessation of circulation, rSO2 levels dropped but remained above zero, indicating potential limitations in accurately detecting severe hypoxia. This case study demonstrated the effectiveness of the O3™ system in monitoring rSO2 in such critical situations, uniquely supported by the cerebral haemoglobin index, oxygenated haemoglobin index, and deoxygenated haemoglobin index. The findings emphasise the importance of understanding oxygen transport mechanisms and haemoglobin affinity to accurately interpret NIRS data, especially in brain-dead patients and organ donation procedures.